Impact of Dehanding and Growth Regulators Spray on Yield Characteristics of Banana cv. Grand Naine - Pavani, K.; Susila, T.; Prasad, M. Siva; Kumar, Y. Sharat (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during August, 2023–May, 2024 at Banana Research Station, Pulivendula, Andhra Pradesh, India to study the effect of dehanding and growth regulators spray on yield characteristics of Banana cv. Grand Naine. The experiment consists of four dehanding treatments (D1: 8 hands after dehanding, D2: 9 hands after dehanding, D3: 10 hands after dehanding, D4: no dehanding) and three growth regulator sprays (T1: GA3 50 ppm+CPPU 4 ppm, T2: GA3 100 ppm+CPPU 4 ppm, T3: water spray). The results showed that maximum finger length (21.23 cm), girth (11.84 cm), diameter (4.08 cm), finger weight (182.20 g) and hand weight (2.34 kg) were recorded in bunches retained with 8 hands after dehanding. Bunches retained with 10 hands after dehanding produced the highest bunch weight (23.57 kg) and maximum yield ha-1 (78.55 t ha-1). The application of GA3 50 ppm+CPPU 4 ppm recorded maximum finger length (20.40 cm), girth (10.97 cm), diameter (3.10 cm), finger weight (176.80 g), hand weight (2.20 kg), bunch weight (22.73 kg) and yield ha-1 (75.77 tons). The interaction of retaining 8 hands bunch-1 after dehanding and bunch spray with GA3 50 ppm+CPPU 4 ppm resulted in maximum finger length (22.61 cm), girth (12.58 cm), diameter (4.36 cm), finger weight (192.60 g), hand weight (2.54 kg). Maximum bunch weight (24.32 kg) and total yield ha-1 (81.05 tons) was found in combination of retaining 10 hands bunch-1 after dehanding with bunch spray of GA3 50 ppm+CPPU 4 ppm.